Prototype of a Multimodal and Multichannel Electro-Physiological and General-Purpose Signal Capture System: Evaluation in Sleep-Research-like Scenario - Pablo Cevallos-Larrea; Leimer Guambaña-Calle; Danilo Andrés Molina-Vidal; Mathews Castillo-Guerrero; Aluizio d’Affonsêca Netto; Carlos Julio Tierra-Criollo (Sensors)
The simultaneous analysis of electrophysiological signals from various physiological systems, such as the brain, skeletal muscles, and cardiac muscles, has become increasingly necessary in both clinical and research settings. However, acquiring multiple modalities of electrophysiological data often necessitates the use of diverse, specialized technological tools, which can complicate the establishment of a comprehensive multimodal experimental setup. This paper introduces a prototype system, named the Multimodal–Multichannel Acquisition Module—MADQ, designed for the simultaneous acquisition of multimodal and multichannel electrophysiological and general-purpose signals. The MADQ comprises three distinct capturing blocks, each equipped with separate reference circuits, supporting a total of up to 40 electrophysiological input channels, alongside 4 channels of analog input and 4 channels of digital input signal. The system is capable of sampling frequencies up to 16 kHz. Key features of the MADQ include individually configurable bipolar recording, lead-off detection capability, and real-time online filtering. The system’s functional performance was characterized through metrics such as Input-Referred Noise (IRN), Noise-Free Bits (NFB), and Effective Number of Bits (ENOB) across varying gain and sampling frequencies. Preliminary experiments, conducted in a setup emulating a sleep study with auditory evoked potential detection, demonstrate the system’s potential for integration into multimodal experimental scenarios.